Biofabrication of a co-culture system in an osteoid-like hydrogel matrix. (11th May 2017) - Zehnder, Tobias; Boccaccini, Aldo R; Detsch, Rainer
Abstract: Biofabrication aims to develop functional, biological constructs using automated processes (additive manufacturing, AM) involving different cell types and biomaterials (Groll et al 2016 Biofabrication 13001 1–6). As bone tissue is based on the crosstalk between osteoblasts and osteoclasts at least, evaluating cell–cell and cell–material interactions is of interest to understand bone remodeling. There is increasing interest in the role of osteoclasts not only considering bone resorption, but also their influence on the proliferation, migration and differentiation of osteoblasts. Osteoid-like, non-mineralized matrix is used here for the 3D cultivation of osteoblast and osteoclast progenitor cells to evaluate interactions in an early stage of bone formation. The AM technology bioplotting was used to tailor a 3D environment with defined properties. These results could be helpful to transfer this approach to the fabrication of bone tissue in regenerative medicine approaches. Gelatin is derived from collagen, which is the main phase of osteoid. Oxidized alginate–gelatin crosslinked hydrogel was used to immobilize osteoblastic (ST2) and osteoclastic (RAW) progenitor cells. Cell viability and number, the expression of different proteins like alkaline phosphatase (ALP), osteopontin (OPN) and tartrate resistant acid phosphatase (TRAP) were investigated. Release of vascular endothelial growth factor (VEGF) by the immobilized cells was analyzed. Microscopy techniques were used to evaluate cell morphology during an incubation period of 21 days. The biofabrication process was compatible with the cells. Cells migrated, proliferated and expressed their specific proteins indicating cell differentiation. The co-culture showed increased OPN concentration, which is a major protein of the osteoid involved in the mineralization process. TRAP activity was increased compared to single culture. ST2 single culture showed higher ALP activity compared to the co-culture. VEGF concentration of the co-culture was strongly increased. The results indicate the importance of using co-cultures to fabricate bone tissue by biofabrication. Especially the influence of the osteoblast/osteoclast crosstalk, in an early stage of bone formation, is shown here, using a 3D hydrogel based cell culture model created by biofabrication.